Oligoclonal CD4+CXCR5+ T cells with a cytotoxic phenotype appear in tonsils and blood - Liang, Chunguang; Spörl, Silvia; Xiao, Yin; Habenicht, Katharina M.; Haeusl, Sigrun S.; Sandner, Isabel; Winkler, Julia; Strieder, Nicholas; Eder, Rüdiger; Stanewsky, Hanna; Alexiou, Christoph; Dudziak, Diana; et al. (Communications Biology, 2024)
Most subsets of CD4+ T-follicular helper cells occur in blood and tonsils, but location enforces specific gene expression. One subtype reveals a cytotoxic phenotype, is circulating or extrafollicular, oligoclonal and shares TCRs with other clusters.
CRIS-Team Scopus Importer:2024-07-26